1983
DOI: 10.1002/jez.1402270317
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of β‐endorphin levels in regenerating and nonregenerating vertebrates

Abstract: The mean plasma level of beta-endorphin in the newt, Notophthalmus viridescens, as measured by radioimmunoassay, is significantly higher than the circulating levels of beta-endorphin in the anuran, Rana pipiens, and in mammals (humans and mice). The newt beta-endorphin level is found to be 6-fold greater than mammalian levels and three times greater than the levels observed in Rana pipiens. The high levels are maintained in the newt throughout limb regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A few of these diabetic animals exhibiting total arrest in limb and tail regenerates eventually recovered from diabetes and showed signs of reactivation of blastemal formation as late as 44 days postamputation. Subsequent histological examination revealed large hypertrophied islets in the pancreas, strongly suggestive of a correlation between regeneration of the islets and reactivation of blastemal cell accumulation (25). In this regard, we also observed that somatostatin, a hypothalamic factor that has a known inhibitory effect on the release of INS, GH, thyroidstimulating hormone, PRL, and glucagon in mammals, also inhibits limb and tail regeneration in the adult newt (28).…”
Section: In Vivo Experimentsmentioning
confidence: 71%
See 3 more Smart Citations
“…A few of these diabetic animals exhibiting total arrest in limb and tail regenerates eventually recovered from diabetes and showed signs of reactivation of blastemal formation as late as 44 days postamputation. Subsequent histological examination revealed large hypertrophied islets in the pancreas, strongly suggestive of a correlation between regeneration of the islets and reactivation of blastemal cell accumulation (25). In this regard, we also observed that somatostatin, a hypothalamic factor that has a known inhibitory effect on the release of INS, GH, thyroidstimulating hormone, PRL, and glucagon in mammals, also inhibits limb and tail regeneration in the adult newt (28).…”
Section: In Vivo Experimentsmentioning
confidence: 71%
“…Hypophysectomized animals do not normally feed; starvation, together with the absence of ACTH-stimulated glucocorticoids, would explain the nonfunctional state of the pancreas. Hypophysectomized newts exhibited an extreme delay or total arrest of limb and tail regeneration (5,6). Second, sublethal pancreatectomy or alloxan treatment, resulting in a diabetic condition in newts, also resulted in greatly delayed and abnormal limb and tail regenerates.…”
Section: In Vivo Experimentsmentioning
confidence: 97%
See 2 more Smart Citations
“…Possessing the triggering mechanism, the drug induces a cascade of in£ammatory-reparative reactions, which reduce the duration of all healing stages (Shekhter et al, 1988;Kohl et al, 1989). It has been found that the m-opiate receptor ligand b-endorphin has an important role in limb regeneration in nonmammalian vertebrates (Vethamany-Globus et al, 1983). Another group (Soledad Cepeda et al, 1993) examined the interactions between exogenous opioid analgesia and endogenous opioid generation at a site of burn-induced tissue injury.…”
Section: Discussionmentioning
confidence: 99%